Petroleum radiation processing - Zaikin, Yuriiy (CRC Press, 2014)
"This book is a summary of the research progress in the field of petroleum radiation processing, giving rise to technology that offers the highest energy savings and lowest capital and operational expenses compared with any existing methods for oil refining. The theoretical part of this book sets out important problems in self-sustaining cracking reactions in hydrocarbons. The next part provides a systematic description of the most important experiments on radiation cracking. The concluding part summarizes progress in the development of new radiation technologies for oil upgrading and deep processing"--